2015
DOI: 10.1186/s40661-015-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cervical cancer on quality of life: beyond the short term (Results from a single institution)

Abstract: BackgroundCervical cancer (CC) is one of the most widespread gynecological malignancies in women worldwide. Treatment strategies and screening modalities have largely evolved these past years resulting in an improvement of survival. However, treatment modalities are associated with long term side effects that significantly impacts quality of life (QOL) in cervical cancer survivors. The aim of this study is to evaluate QOL (General and sexual QOL) in cervical cancer survivors up to 10 years after the diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 23 publications
9
54
1
6
Order By: Relevance
“…The general health status/QoL mean score was low, which is consistent with Iranian and Chinese findings [18,19], but lower than Brazilian and Indian studies [20,21]. The possible reasons could be the cultural belief, distorted perception of survivors regarding their illness, and lower self-esteem [22]. In this study, diarrhea was among the least reported symptoms among cervical cancer survivors, which is similar to the study conducted in India [23].…”
Section: Discussionsupporting
confidence: 88%
“…The general health status/QoL mean score was low, which is consistent with Iranian and Chinese findings [18,19], but lower than Brazilian and Indian studies [20,21]. The possible reasons could be the cultural belief, distorted perception of survivors regarding their illness, and lower self-esteem [22]. In this study, diarrhea was among the least reported symptoms among cervical cancer survivors, which is similar to the study conducted in India [23].…”
Section: Discussionsupporting
confidence: 88%
“…Once posttreatment failure occurs, prognosis becomes worse: the 1-year survival rates of patients with such failures are less than 20% [ 6 ]. Moreover, various side effects are produced that can greatly influence a patient's quality of life [ 7 ]. Despite these alarming facts, efficient methods of treatment are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies were conducted in the Republic of South Africa. [ 27 28 ] Single studies were conducted from each of the following countries: Nigeria,[ 29 ] Kenya,[ 30 ] Sudan,[ 19 ] Uganda,[ 31 ] Morocco,[ 32 ] and Zambia. [ 33 ] In the following section, we present a synthesis of included studies.…”
Section: Resultsmentioning
confidence: 99%